Formulating octyl methoxycinnamate in hybrid lipid-silica nanoparticles: An innovative approach for UV skin protection - Andreani, T.; Dias-Ferreira, J.; Fangueiro, J. F.; Souza, A. L.R. [UNESP]; Kiill, C. P. [UNESP]; Gremião, M. P.D. [UNESP]; García, M. L.; Silva, A. M.; Souto, E. B. (Elsevier, 2020)
Sunscreens have been employed on daily skin care for centuries. Their role in protecting the skin from sun damage, avoiding accelerated photoaging and even limiting the risk of development of skin cancer is unquestionable. Although several chemical and physical filters are approved as sunscreens for human use, their safety profile is dependent on their concentration in the formulation which governs their acceptance by the regulatory agencies. A strategic delivery of such molecules should provide a UV protection and limit the skin penetration. Solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC) may offer an alternative approach to achieve a synergistic effect on the UV protection when loaded with sunscreens as particles themselves also have a UV light scattering effect. Besides, the lipid character of SLN and NLC improves the encapsulation of lipophilic compounds, with enhanced loading capacity. Silica nanoparticles have also been employed in sunscreen formulations. Due to the formed sol-gel complexes, which covalently entrap sunscreen molecules, a controlled release is also achieved. In the present work, we have developed a new sunscreen formulation composed of hybrid SLN-Silica particles loaded with octyl methoxycinnamate (Parsol®MCX), and their further incorporation into a hydrogel for skin administration. Hybrid SLN-silica particles of 210.0 ± 3.341 nm of mean size, polydispersity below 0.3, zeta potential of ca. |7| mV, loading capacity of 19.9% and encapsulation efficiency of 98.3% have been produced. Despite the slight negative surface charge, the developed hybrid nanoparticles remained physicochemically stable over the study period. Turbiscan transmission profiles confirmed the colloidal stability of the formulations under stress conditions. The texture profile analysis of Parsol-SLN and Parsol-SLN-Si revealed semi-solid properties (e.g. adhesiveness, hardness, cohesiveness, springiness, gumminess, chewiness, resilience) suitable for topical application, together with the bioadhesiveness in the skin of pig ears. The non-irritation profile of the hybrid nanoparticles before and after dispersion into Carbopol hydrogels was confirmed by HET-CAM test.

Pharmaceutical science, Pharmaceutical chemistry, Nanotechnology, Octyl methoxycinnamate, Solid lipid nanoparticles, SLN, Silica hybrid nanoparticles, Sunscreens, Hydrogel
Keywords: Hydrogel; Nanotechnology; Octyl methoxycinnamate; Pharmaceutical chemistry; Pharmaceutical science; Silica hybrid nanoparticles; SLN; Solid lipid nanoparticles; Sunscreens